Kafala and Spanish law after reform of the law 54/2007. On the auto AP León of 27th June 2019 - Guzmán Zapater, Mónica (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
Non recognition of Kafala between Moroquians citizens as basis to constitute international adoption. Legal framework and Prohibition in Article 19.4 International Adoption Law in order to avoid international adoptions wether personal law forbids such a mesure, it´s directly adressed to authorities and just legal exceptions should be admitted.